Efektivitas Komunikasi Kepemimpinan Transformasional Ketua RT Terhadap Partisipasi Warga Di Kabupaten Bogor (Communication Effectiveness Transformational Leadership Head of the Neighbourhood Community Against Citizens Participation in Kabupaten Bogor) - Naila Vellayati; Sarwititi Sarwoprasodjo; Cahyono Tri Wibowo (Institut Pertanian Bogor, 2016)
The importance of communication development can help people or parties involved in the development to stay on its tracks and create independence. The aim of this study consists of 1) Analyzing the relationship credibility of Women and Men Head of the Neighbourhood Community 2) Analyzing the relationship between the meeting intensity of the Women and Men Head of the Neighbourhood Community 3) To analyze the relationship of transformational leadership. The unit of analysis in this study comprises of 38 Women and Men Head of the Neighbourhood Community. The location was chosen deliberately, namely the District Dramaga. Parung and Ciomas. The sampling technique used was sensus and quota sampling by Spearman correlation using different teststo see the differences between Women and Men Head of the Neigbourhood Community. Women Head of the Neighbourhood Community shows significant relationships in the credibility, the intensity of the meeting, and transformational leadership. Head of the Neighbourhood Community Men related real on transformational leadership. It said that women and men do not differ regarding the actual transformational leadership related to the level of participation. It happens because when meeting citizens given the opportunity to provide opinions, advice, ideas and information, and if the activities carried out concerning the interests of the shared environment and a sense of solidarity among citizens.Keywords:Communication Development, Rural Development, Neigbourhood Community, TransformationalLeadership, Participation